The effects of initiating a 24-hour fast with a low versus a high carbohydrate shake on glycemic control in older adults: a randomized crossover study - Elizabeth Z. Gipson; Landon S. Deru; Parker G. Graves; Cameron G. Jacobsen; Neil E. Peterson; Bruce W. Bailey (Nutrition & Metabolism)
Abstract Purpose This study measured the impact of macronutrient composition of a pre-fast meal on time-to-ketosis and other metabolic indicators of glycemic control during a 24-hr fast within a population of older, sedentary, overweight adults. Methods Twenty-four adults who were over the age of 50, sedentary (< 150 min of weekly exercise), and overweight (BMI ≥ 27) participated in a randomized crossover study. Each of these inclusion criteria have been shown to increase the risk for the development of chronic diseases. Participants began each 24-hr fast with either a high carbohydrate/low fat/moderate protein (HC/LF) or an isocaloric low carbohydrate/high fat/moderate protein (LC/HF) shake. Metabolic indicators included subcutaneous glucose readings every 15 min throughout the study, capillary beta-hydroxybutyrate (BHB), and plasma concentrations of insulin, glucagon, glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic peptide (GIP). Measurements of these hormones took place at 0, 1, 24, and 48 h, and BHB measurements took place at 0, 1, 4, 8, 12 and 24 h. Results Glucose levels were higher in the HC/LF group 15 min to 2.25 h after fast initiation (p < 0.05 for all). There was a significant condition by time interaction for BHB (F = 3.84, p < 0.01). Nutritional ketosis (BHB ≥ 0.5 mmol/L) was reached on average by 12 h in the LC/HF condition but was not reached at any point during the fast on average in the HC/LF condition. An hour after consuming the LC/HF shake insulin was 41.9% lower (t = 6.13, p < 0.01), glucagon 23.6% higher (t = -4.72, p < 0.01), GLP-1 26.8% higher (t = -5.16, p < 0.01), and GIP 34.4% higher (t = -3.41, p < 0.01) compared to the HC/LF shake. Conclusion A low carbohydrate pre-fast meal can reduce time-to-ketosis in older, sedentary, overweight adults. Those looking to improve glycemic control through fasting or time-restricted eating interventions may consider the macronutrient composition of their pre-fast meal to improve its efficacy.